Effect of chitosan-tripolyphosphate to suppress anthracnose (Colletotrichum spp.) in post-harvest chili - Yadi Suryadi; Dwi Ningsih Susilowati; Jajang Kosasih; Titi Tentrem; I Made Samudra (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Anthracnose disease (Colletotrichum spp.) in chili can lead to low fruit quantity and quality from planting to the postharvest stage. The environmentally friendly management using chitosan (CS) is expected to suppress anthracnose disease and increase the shelf-life of chili. This study aimed to determine the effect of the chitosan-tripolyphosphate (CS-TPP) to suppress anthracnose on chili during postharvest storage through in-vitro and in-vivo assays. In the in-vitro assay, CS-TPP solution with a ratio of [5:2] and [3:1] was applied into a warm Potato Dextrose Agar (PDA) medium. It was grown by Colletotrichum pathogen, while on in vivo assay, CS-TPP was applied to chili fruit before being inoculated by the pathogen. A control treatment was prepared without CS-TPP application. Results revealed that the CS-TPP ratios affected the growth of Colletotrichum spp. at the in-vitro assay. The CS-TPP [5:2] ratio was more effective than CS-TPP [3:1] in reducing the growth of Colletotrichum spp. with the fungal inhibition of 62,65% and 55,56%, respectively, compared to the control treatment. Moreover, it also showed anthracnose disease suppression on chili fruit of 51%, and 29%, respectively, compared to control treatment at in-vivo assay. This study showed the potential use of CS-TPP as a coating application for anthracnose disease management on storage chili, however further study such as viability and longevity of formula need to be done.